Fatty acids used as phase change materials (PCMs) for thermal energy storage in building material applications - Chuah, T. G.; Rozanna, D.; Choong, Thomas Shean Yaw, Assoc. Prof. Dr.; Sa'ari, M.; Salmiah, A. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/